Pertimbangan Hakim dalam Menetapkan Nafkah terhadap Istri Pasca Perceraian - Patimah; Kiljamilawati; Tegar, Israh Ramdana (Jurusan Hukum Acara Peradilan dan Kekeluargaan, 2023)
Determination of the burden of income by the husband on the wife When a divorce occurs, it is the authority of the judge in determining the amount, and in practice it varies because there are no special rules governing in detail for the judge in determining the amount of income for the wife This article tries to explain the judge's considerations or interpretations in determining the amount of maintenance for a wife after divorce which is based on the decision of the Pangkajene Religious Court with case number: 248/Pdt.G/2023/PA.Pkj regarding how the judge then tries to protect women's rights. . This article will analyze the judge's decision which imposes an obligation on the husband to fulfill obligations to his wife in the form of payment of iddah living, madliyyah living, and mut'ah.